A space syntax comparative study on sustainable historic districts: Al-Fahidi, UAE and Al-Darb Al-Ahmar, Egypt - Iman Ibrahim; Imene Soussi; Hadeel Al Qaysi (City, Territory and Architecture)
Abstract The research focuses on spatial dynamics in two major historical districts: Al-Fahidi in Dubai, United Arab Emirates (UAE) and Al-Darb Al-Ahmar in Cairo, Egypt. Both are historic areas of great cultural history and architectural significance, but each faced different challenges when it came to urban modernization and a great number of visitors and tourists. Based on the use of Space Syntax as its main analytical tool, this research investigates street networks, patterns of visibility, and spatial integration to clarify how far these configurations impact the dynamics of social interaction, the conservation of culture, and city development projects. The results show the differences in how the two quarters balance heritage with development. Al Fahidi illustrates the potential of adaptive reuse in converting historic structures into lively cultural and artistic centers. Conversely, Al-Darb Al-Ahmar has been able to conserve a strong relationship with traditional community-based activities, like crafts and local trading in its spatial structure. The findings underscore the essential importance of spatial arrangements in facilitating both tangible heritage preservation and the continuity of intangible cultural practices, thereby providing viable strategies to align with sustainable development goal 11 (SDG 11) related to sustainable urban development and community enhancement. The aim is to fill the gap in the comparative analysis of historic districts by integrating spatial data with aspects of cultural sustainability. It gives very important recommendations to urban planners and policymakers, highlighting the importance of including cultural identity within modern development frameworks. Using Space Syntax as a methodology enriches the research contribution to the global debate on how heritage preservation could be integrated with social cohesion and sustainable development.